Completing Wallace's journey - Kennedy, Jonathan D.; Fjeldså, Jon (Science (American Association for the Advancement of Science), 2020)
A global inventory of species diversity is critical for understanding the evolution of life on Earth British naturalist Alfred Russel Wallace developed the theory of evolution as a consequence of the taxonomic discoveries made during his expeditions across the Indonesian archipelago in the 19th century. From his collections, thousands of new species have been described, including around 2% of all living bird species. Birds are one of the most comprehensively documented organismal groups, but multiple new species continue to be described yearly, and at an increasing rate. Nearly all recent avian species discoveries come from disjunct geographic locations. However, on page 167 of this issue, Rheindt et al. ( 1 ) describe five new species and five subspecies from three islands off the eastern coast of Sulawesi, Indonesia. This is the largest number of new species descriptions from a restricted geographic locality in over a century and highlights the importance of documenting biodiversity today, given the environmental threats that could condemn many as yet unidentified taxa to extinction.